Toward sub‐micro‐XRF working at nanometer range using capillary optics. (19th July 2013) - Dehlinger, M.; Fauquet, C.; Jandard, F.; Bjeoumikhov, A.; Bjeoumikhova, S.; Gubzhokov, R.; Erko, A.; Zizak, I.; Pailharey, D.; Ferrero, S.; Dahmani, B.; Tonneau, D.
<x xml:space="preserve">Abstract</x> Capillary optics are used for X‐ray fluorescence micro‐analysis using the Cu Kα line provided by a rotating anode. The excitation beam is focused using a polycapillary lens on a Co–Ti sample. Cylindrical glass capillaries of various diameters are fitted to the X‐ray detector (Energy Dispersive X‐Ray (EDX) analyzer) and displaced along the irradiated zone of the sample. The fluorescence is studied as a function of capillary position. Good agreement is found between experimental and calculated lateral widths of the fluorescence collection, taken into account the cylindrical capillary critical angles relevant in the experiment. The influence of the cylindrical capillary diameter on the signal level detected is studied to estimate the possibility of lateral resolution increase of X‐ray fluorescence technique both in‐lab and in synchrotron environment. Copyright © 2013 John Wiley & Sons, Ltd.